Management of Complex Mandible Fractures - Shokri, Tom; Misch, Emily; Ducic, Yadranko; Sokoya, Mofiyinfolu (Facial Plastic Surgery, 2019)
Mandible fractures represent a common sequela of craniomaxillofacial trauma encountered by reconstructive surgeons. Management of complex mandibular fractures, and reestablishment of the occlusal relationship, represents a challenging reconstructive endeavor for even the most skilled surgeon. In this article, the authors review the treatment options for particularly complex presentations of this injury pattern.
Keywords: comminuted mandible fracture; atrophic mandible fractures; mandible continuity defect; mandible fractures